(untitled) (Revista Internacional de Ingeniería de Estructuras, 2023)
Argentina has a wide spectrum of seismic hazard, being very high in the central west and attenuating towards the east. This is the reason for the need of having updated regulations for the seismic resistant design of structures. The National Institute for Seismic Prevention is in charge of drafting the seismic-resistant regulations in our country and, for the design of reinforced concrete structures under seismic actions, INPRES-CIRSOC 103-II (2005) is in force. In 2020, a new version was put under national public discussion and, since 2021, it is in the process of approval, maintaining the philosophy of design by capacity. This paper analyzes and compares the changes between both versions and, in some aspects, with other international standards. Important changes in material requirements, longitudinal reinforcement amounts of beams and partitions are highlighted. The changes are shown with graphs and comparative tables between both versions